The study of association of serum ischemia-modified albumin and prediabetes in women: A case–control study - Ahirwar, Ashok Kumar; Jain, Rashmi; Choubey, Udit; Jain, Ankit; Takhelmayum, Roshan; Sakarde, Apurva; Pawar, Akash Mahadeo; Rathod, Bharatsing Deorao (Asian Journal of Medical Sciences, 2022)
Background: Prediabetes, diabetes, and their associated complications adversely affect women’s health worldwide. Women in the reproductive age group are more prone for developing diabetes and its associated complications such as gestational diabetes and infertility. Hence, it is the need of the hour to diagnose women at risk of pre-diabetes. Oxidative stress, ischemia, and hypoxia have been suggested as important factors in developing prediabetes and its sequels. Aims and Objectives: The present study aimed to study the association of serum ischemia-modified albumin (IMA), namely, a marker of oxidative stress, ischemia, and hypoxia with prediabetes in the women of reproductive age group. Materials and Methods: The present study was carried out in 50 females in the reproductive age group of 19–45 years. The study population was further sub-divided into two groups: Group I consisted of 25 prediabetic patients and Group II consisted of 25 healthy controls. Serum samples of the subjects were analyzed for serum IMA, blood sugar profile, and other routine biochemistry tests. Results: The present study showed that mean serum IMA was raised in prediabetic group as compared to healthy controls. The serum IMA also positively correlated with blood sugar profile. Conclusion: Increased serum IMA could be used as a biomarker for predicting prediabetes in females of reproductive age group. This, in turn, would be helpful in preventing the burden of various complications known to occur in the natural course of prediabetes and diabetes.